It Is Time to Move Forward…On the Basis of Sex: The Impact of Bostock v. Clayton County on the Interpretation of “Sex” under Title IX - Abbey Widick (Washington University Journal of Law and Policy, 2022)
In 1972, Congress passed Title IX of the Education Amendments, explicitly prohibiting sex-based discrimination in an education program or activity. However, there are still questions over the legal interpretation of sex-based discrimination in Title IX. This Note proposes explicitly prohibiting discrimination based on sexual orientation or gender identity in educational institutions under Title IX’s prohibition on sex-based discrimination. Widick frames her argument through a comparison to Title VII of the Civil Rights Act of 1964 and the Supreme Court’s ruling in Bostock v. Clayton County, Georgia, which found that the prohibition against sex discrimination in Title VII includes discrimination on the basis of sexual orientation and gender identity. Widick argues that following the holding in Bostock, and recent circuit court cases interpreting sex discrimination under Title IX, other circuit courts should follow suit and allow claims for gender identity and sexual orientation discrimination under Title IX. The Note concludes by emphasizing the positive policy implications of interpreting gender identity and sexual orientation discrimination as forms of sex discrimination. Now, in the next frontier of the Civil Rights movement, it is once again time to move forward, this time on the basis of sex.
Keywords: Title IX of the Education Amendments; Sex-Based Discrimination; Sexual Orientation; Gender Identity; Bostock v. Clayton County Georgia; Title VII of the Civil Rights Act of 1964